2021
DOI: 10.1186/s13054-021-03720-4
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning identifies ICU outcome predictors in a multicenter COVID-19 cohort

Abstract: Background Intensive Care Resources are heavily utilized during the COVID-19 pandemic. However, risk stratification and prediction of SARS-CoV-2 patient clinical outcomes upon ICU admission remain inadequate. This study aimed to develop a machine learning model, based on retrospective & prospective clinical data, to stratify patient risk and predict ICU survival and outcomes. Methods A Germany-wide electronic registry was established to pseudon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 36 publications
6
32
0
2
Order By: Relevance
“…Machine learning includes many methods that could be utilized in the ICU, and these vary in their complexity [6] . Several studies used different complex machine learning models to predict ICU admission and mortality especially during the COVID-19 pandemic [7] , [8] . A decision tree (DT) is a simple and intuitive machine learning method that provides sequential nonlinear analysis in algorithmic relationship of combined risk factors to produce a quantitative percentage of sensitivity to mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning includes many methods that could be utilized in the ICU, and these vary in their complexity [6] . Several studies used different complex machine learning models to predict ICU admission and mortality especially during the COVID-19 pandemic [7] , [8] . A decision tree (DT) is a simple and intuitive machine learning method that provides sequential nonlinear analysis in algorithmic relationship of combined risk factors to produce a quantitative percentage of sensitivity to mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have used various machine learning algorithms for analyzing COVID-19 patients’ clinical data and providing disease prognosis [ 9 11 ]. Studies have also been conducted to compare the performance of different machine learning algorithms for multivariable mortality risk prediction [ 12 14 ]. Kuno et al built a model based on Light Gradient Boosted Machine (LGBM) for predicting in-hospital mortality of COVID-19 patients administered with steroids and remdesivir.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance, Tang et al highlighted in a study in 2020 the importance for IL-6 and PCT measurement as predictive biomarkers for COVID-19 severity [42] . Furthermore, a recently published multicenter COVID-19 cohort study identified higher PCT, CRP and interleukin-6 values as three out of ten most important predictive values for ICU mortality by machine learning model in 1039 patients [43] .…”
Section: Discussionmentioning
confidence: 99%